Second-generation high-temperature superconducting coils and their applications for energy storage - Yuan, Weijia; SpringerLink (Online service). (London New York Springer, 2011)
Second-Generation High-Temperature Superconducting Coils and Their Applications for Energy Storage addresses the practical electric power applications of high-temperature superconductors. It validates the concept of a prototype energy storage system using newly available 2G HTS conductors by investigating the process of building a complete system from the initial design to the nal experiment. It begins with a clear introduction of the related background and then presents a comprehensive design of a superconducting energy storage system that can store maximum energy using a limited length of superconductors. The author has created a modeling environment for analysis of the system and also presents experimental results that are highly consistent with his theoretical calculations.
1. Introduction -- 2. Background of Superconductors -- 3. Development of SMES Systems -- 4. Coil Design -- 5. Modelling of Superconducting Pancake Coil -- 6. Coil Tests and Applications for SMES -- 7. Conclusions.
Electronic reproduction.
Keywords: High temperature superconductors; Magnetic energy storage; Electronic books